PENGEMBANGAN KARTU KENDALI KEDISIPLINAN SISWA DALAM PENILAIAN SIKAP (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2016)
The purpose of this research to develop a discipline control card that serves as a medium assessment attitude with development model refers to the SDLC (System Development Life Cycle)-waterfall starting from the analysis, design, implementation, testing, and maintenance. The technique of collecting data using interviews, observations, questionnaires, and documentation. The results showed that the material experts validation get a score of 4.0 with a very good category. Media expert validation results to get a score of 3.7 with a very good category. Rate teachers use to get a score of 3.4 in the category of good. Based on trial results using a control card the first day use get a total score of 4525 and continues to increase with an average progress score of 223 points per day until on the sixth day of use get a total score of 6534. This means control cards can increase the discipline of students, Based on the results of this study concluded that student discipline worthy of a control card is used as an instrument ratings attitude. Researchers hope the school can use the controller card in learning.